"Pi of the Sky" Detector. (15th December 2009) - Małek, Katarzyna; Batsch, Tadeusz; Czyrkowski, Henryk; Ćwiok, Mikołaj; Dąbrowski, Ryszard; Dominik, Wojciech; Kasprowicz, Grzegorz; Majcher, Ariel; Majczyna, Agnieszka; Mankiewicz, Lech; Nawrocki, Krzysztof; Pietrzak, Robert; et al.
Abstract : "Pi of the Sky" experiment has been designed for continuous observations of a large part of the sky, in search for astrophysical phenomena characterized by short timescales, especially for prompt optical counterparts of Gamma Ray Bursts (GRBs). Other scientific goals include searching for novae and supernovae stars and monitoring of blasars and AGNs activity. "Pi of the Sky" is a fully autonomous, robotic detector, which can operate for long periods of time without a human supervision. A crucial element of the detector is an advanced software for real-time data analysis and identification of short optical transients. The most important result so far has been an independent detection and observation of the prompt optical emission of the "naked-eye" GRB080319B.